Case Series of Primary Testicular Lymphoma: Insights into a Rare Condition - Chaudhary, Kiran G; Tripathy, Amruta; Bagri, Puneet Kumar; Jain, Himanshi Avinash (Indian Journal of Case Reports, 2025)
Primary testicular lymphoma (PTL) is a rare extranodal type of non-Hodgkin’s lymphoma (NHL), accounting for